Experimental investigation of frost retardation for superhydrophobic surface using a luminance meter. (August 2015) - Kim, Donghee; Kim, Hisuk; Kim, Sun Woo; Kim, Dong Rip; Lee, Kwan-Soo
Highlights: This study investigated the phenomena of frost retardation. A novel experimental method using a luminance meter is introduced. This experimental method is able to define the frost stages quantitatively. The 10 different water contact angle were used to analyze the frost retardation. Abstract: We experimentally investigated the phenomena of frost retardation in terms of the heat exchanger fins with various water contact angles under normal air-source heat-pump operating conditions. We first introduced a new experimental method using a luminance meter, which measured the light intensity from the surface, and determined the phase-change time, for quantitatively defining the frost stages. The phenomena of frost retardation was analyzed for 10 samples with different water contact angles (75°–160°) at different refrigerant temperatures. When the refrigerant temperature was −10 °C or −12 °C, the effect of frost retardation increased remarkably with superhydrophobic surfaces. However, when the refrigerant temperature was −8 °C, the effect of superhydrophobicity diminished at water contact angles greater than 150°.